On the geographic and cultural determinants of bankruptcy - Stefan Buehler; Christian Kaiser; Franz Jaeger (University of Zurich, Socioeconomic Institute, 2007)
This paper examines the role of geography and culture in explaining bankruptcy. We adopt survival analyses to model the bankruptcy risk of a firm, allowing for time-varying covariates. Based on a large sample from all major sectors of the Swiss economy, we find the following results: (i) The geographic location of a firm, which is characterized using a core-periphery approach, has a significant impact on its bankruptcy risk; (ii) Variables proxying for the cultural environment of a firm have significant explanatory power; (iii) The results of the previous literature on the standard determinants of bankruptcy are confirmed.
Keywords: C41; R10; Z10; 330; bankruptcy; geography; culture; exit; Insolvenz; Geographie; Kultur; Schätzung; Schweiz